ASSESSMENT OF THE ASSOCIATION BETWEEN DUST STORMS AND COVID-19 INFECTION RATE IN SOUTHWEST IRAN - Broomandi, Parya; Crape, Byron; Jahanbakhshi, Ali; Janatian, Nasime; Nikfal, Amirhossein; Tamjidi, Mahsa; Kim, Jong R.; Middleton, Nick; Karaca, Ferhat (Environmental Science and Pollution Research, 2022)
This study assesses a plausible correlation between a dust intrusion episode and a daily increase in COVID-19 cases. A surge in COVID-19 cases was observed a few days after a Middle East Dust (MED) event that peaked on 25th April 2020 in south west Iran. To investigate potential causal factors for the spike in number of cases, cross-correlations between daily combined aerosol optical depths (AODs) and confrmed cases were computed for Khuzestan, Iran. Additionally, atmospheric stability data time series were assessed by covering before, during, and after dust intrusion, producing four statistically clustered distinct city groups. Groups 1 and 2 had diferent peak lag times of 10 and 4-5 days, respectively. Since there were statisti cally signifcant associations between AOD levels and confrmed cases in both groups, dust incursion may have increased population susceptibility to COVID-19 disease. Group 3 was utilized as a control group with neither a signifcant level of dust incursion during the episodic period nor any signifcant associations. Group 4 cities, which experienced high dust incur sion levels, showed no signifcant correlation with confrmed case count increases. Random Forest Analysis assessed the infuence of wind speed and AOD, showing relative importance of 0.31 and 0.23 on the daily increase percent of confrmed cases, respectively. This study may serve as a reference for better understanding and predicting factors afecting COVID-19 transmission and difusion routes, focusing on the role of MED intrusions.
Keywords: Type of access: Open Access; MED intrusion; Khuzestan; AOD; Atmospheric stability class; SARS-CoV-2; Atmospheric air pollution